Evaluation of the epidural analgesic effect of Nalbuphine, Lidocaine and Nalbuphine-Lidocaine combination in bucks - G.A. Ragab (Beni-Suef University Journal of Basic and Applied Sciences, 2018)
Nalbuphine is a lipophilic opioid which could be used subcutaneously, intramuscularly, intravenously and epidurally in human, dogs and equine but not used in bucks until yet. The aim of the existing study was to compare the analgesic effect of Nalbuphine, Lidocaine and Nalbuphine-Lidocaine combination injected epidurally in bucks. Fifteen adult apparently healthy bucks were used. The animals were randomly divided into three groups (five animals in each one); group (1) was injected with Nalbuphine HCl at a dose 3 mg/kg, group (2) was injected with Lidocaine HCl 2% at a dose 2.5 mg/kg. Finally, group (3) was injected with Nalbuphine-Lidocaine combination at a dose (1.5 mg/kg and 1.25 mg kg, resp.) to evaluate the analgesic effect of each treatment. Onset and duration of analgesia were recorded after each treatment. Respiratory rate, heart rate, rectal temperature and biochemical parameters were recorded for each treatment. The results revealed that, the onset and duration of analgesia respectively were 12 ± 2 min and 200 ± 4 min in group (1), 6 ± 1 min and 80 ± 3 min in group (2) and 8 ± 2 min and 120 ± 5 min in group (3). In Nalbuphine group, No ataxia was observed while mild ataxia was observed in Nalbuphine-Lidocaine combination group but in Lidocaine treated group, sever ataxia was recorded. Heart rate increased at 90–120 and respiratory rate rectal temperature had no any significantly differentiation from baseline of any treatment. Biochemical parameters returned to basal levels through three hours after all treatments. In conclusion, Nalbuphine-Lidocaine combination is useful to perform surgical operations of long duration and had effective analgesia in bucks.